Timing of meristem initiation and maintenance determines the morphology of fern gametophytes. (28th June 2021) - Wu, Xiao; Yan, An; McAdam, Scott A M; Banks, Jo Ann; Zhang, Shaoling; Zhou, Yun
Abstract : The timing of a switch in cell proliferation activities between apical initials and lateral meristems drives morphological variation in fern gametophytes. Abstract: The alternation of generations in land plants occurs between the sporophyte phase and the gametophyte phase. The sporophytes of seed plants develop self-maintained, multicellular meristems, and these meristems determine plant architecture. The gametophytes of seed plants lack meristems and are heterotrophic. In contrast, the gametophytes of seed-free vascular plants, including ferns, are autotrophic and free-living, developing meristems to sustain their independent growth and proliferation. Compared with meristems in the sporophytes of seed plants, the cellular mechanisms underlying meristem development in fern gametophytes remain largely unknown. Here, using confocal time-lapse live imaging and computational segmentation and quantification, we determined different patterns of cell divisions associated with the initiation and proliferation of two distinct types of meristems in gametophytes of two closely related Pteridaceae ferns, Pteris vittata and Ceratopteris richardii . Our results reveal how the simple timing of a switch between two meristems has considerable consequences for the divergent gametophyte morphologies of the two ferns. They further provide evolutionary insight into the function and regulation of gametophyte meristems in seed-free vascular plants.